Modern weapons and military equipment for issue 4/2014 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
New radar technology for enhanced air defence missile system Patriot PAC-3 MSE; Precision-guided air bomb AASM debuted on non-French aircraft; Project for the new Latin American training aircraft; Airbus plans to give Eurofighter maritime strike capability; China plans to build domestic carriers by 2017; Boeing revealed details about Phantom Swift for VTOL X-Plane; Iomax offers the concept of a light aircraft Arckangel; "Simplified" version of the NH90 transport helicopter planned; A prototype S-97 helicopter Raider closer to first flight; Russian T-50 PAK-FA in the phase of weapons flight tests; MANPADS Verba entered service with of Russian paratroopers; Iran launched a new version of the Nazeat rocket; Renault presented demonstrator vehicles 6x6 under the designation BMX-01; Israeli IWI offers a new sniper rifle Day .338; Colt showed assault rifle CK901; Aircraft carrier "Vikramaditya" commisioned with the Indian Navy; The patrol ship of the Navy of Montenegro "Kotor" sails again.